Anti-contamination black thermal control coating and preparation method thereof
By designing a multi-layer structure in the black thermal control coating, including a matching base layer, a high absorption ratio intermediate layer and an easy-to-clean surface layer, the problem of easy staining of the existing coating is solved, and the comprehensive effect of high absorption ratio, long life and good stain resistance is achieved.
Patent Information
- Application Number
- CN202411695510.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-25
AI Technical Summary
The existing black thermal control coatings are prone to contamination in the spatial environment and lack effective repair methods, making it difficult to meet the needs of anti-contamination, long life and high absorption ratio at the same time.
The multi-layer structure design is adopted, including a matching base layer, a high absorption ratio intermediate layer and an easy-to-clean surface layer. By regulating the shape, particle size and content gradient of the filler, a rich micro-nano structure is formed to improve the stain resistance and adhesion of the coating.
High absorption ratio and good anti-fouling properties are achieved, and the coating has long life and high spatial stability in the space environment, and can maintain good thermal radiation performance during service.
Smart Images

Figure CN119680855A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of thermal control coatings, and in particular relates to an anti-fouling black thermal control coating and a preparation method thereof. Background Art
[0002] With the continuous advancement of aerospace technology, the detection range of star sensors has expanded, and the starlight to be detected is getting weaker and weaker. Since there is a lot of stray light from the sun, the earth, etc. in the space environment, it seriously interferes with the normal operation of the star sensor. Therefore, it is necessary to coat the star sensor shield with a black thermal control coating with a high absorption ratio. The interference of stray light on the star sensor is eliminated by multiple absorption of light on the coating. In addition, in order to reduce the possibility of being observed, some satellites need to be coated with a black thermal control coating with a high absorption ratio on the outer surface of the entire satellite to achieve a good extinction effect. This puts forward three requirements for the black thermal control coating: anti-fouling, long life and high absorption ratio.
[0003] Currently, commonly used black thermal control coatings include paint-type high absorption ratio black thermal control coatings, aluminum alloy black anodized coatings, electroplated black nickel coatings, and black polyimide. Aluminum alloy black anodized coatings and electroplated black nickel coatings are both prepared by electrochemical processes, with absorption ratios as high as 0.98 to 0.99. After comprehensive irradiation tests, the coating absorption ratio degrades slightly and has good spatial stability; however, due to the limitations of the preparation process path, the product size requirements are high, and there is a lack of effective repair methods. The absorption ratio of black polyimide film is 0.92, which is relatively low, and has poor resistance to atomic oxygen irradiation, which does not meet the requirements of long life. Paint-type high absorption ratio black thermal control coatings have the advantages of high absorption ratio, easy processing, and cleanability and repairability. They are the preferred material for satellite stray light elimination.
[0004] The existing paint-type black thermal control coating systems are mainly inorganic silicate systems, polyurethane systems and silicone resin systems, which cannot meet the requirements of long life and good adhesion at the same time; at the same time, the filler content in the coating is high, but the scale is relatively single, the micro-nano structure is not sufficiently constructed, and the high content of fillers will reduce the adhesion of the coating. How to balance the absorption ratio and adhesion of the coating is also a key point. For example: The Chinese patent document with publication number CN116855106A and publication date October 10, 2023, entitled "A high-absorption, high-emission, low-condensable volatile inorganic ultra-black thermal control coating and its preparation method" discloses a method for preparing an ultra-black thermal control coating with an inorganic resin and a black filler. The thermal control coating has an absorption ratio of 0.949 and an emissivity of 0.931. The absorption ratio is slightly low, and the surface morphology of the coating is not rich enough; the film-forming material uses a pure inorganic resin system, which is difficult to construct on most non-metallic substrates, and the coating has insufficient substrate adaptability. In addition, because the surface of the existing black thermal control coating has a certain micro-nano structure and is in a "velvet" matte state, it is easy to be contaminated during ground storage and is not suitable for scrubbing with solvents, which affects the light absorption performance of the coating during service. For example: the Chinese patent document with publication number CN117701144A and publication date March 15, 2024, entitled "A mechanically stable ultra-black light-absorbing coating and its preparation method and application" discloses a method of etching the coating with acid and alkali solution to obtain a micro-nano structure, and then fluorinating the etched coating to obtain a thermal control coating with good light absorption performance and certain hydrophobicity, but the coating is not easy to clean, and the problem of easy contamination of the black thermal control coating has not been solved. Summary of the invention
[0005] The purpose of the present invention is to provide an anti-fouling black thermal control coating and a preparation method thereof, to design the coating structure, resin system, and pigment selection and compounding, and to prepare an anti-fouling, long-life, high-absorption black thermal control coating with a three-layer structure, including a matching bottom layer, a high-absorption middle layer, and an easy-to-clean surface layer.
[0006] The above-mentioned purpose of the present invention is mainly achieved through the following technical solutions:
[0007] A method for preparing an anti-fouling black thermal control coating comprises the following steps:
[0008] (1) applying a primer to the surface of a substrate with a coating thickness of 2 to 5 μm, and leaving it in the air at room temperature for 20 to 24 hours to obtain a matching base layer;
[0009] (2) Weighing space-grade silicone resin and micron-grade high-blackness filler at a pigment-base mass ratio of 10:1-12:1, 5:1-8:1 and 2:1-3:1, respectively, adding an organic solvent whose total mass is 8-10 times that of the space-grade silicone resin and the micron-grade high-blackness filler, and uniformly mixing to obtain micron-grade black thermal control coating A1, A2 and A3 components, adjusting the coating-4 cup viscosity of the A1, A2 and A3 components to 20-40s, adding 0.3-1.0% of the mass of the space-grade silicone resin platinum catalyst B component, respectively, and stirring to obtain MC1, MC2 and MC3 black thermal control coatings;
[0010] (3) applying the uniformly mixed black thermal control coatings MC1 to MC3 obtained in step (2) to the matching bottom layer obtained in step (1) in sequence, with an interval of 10 to 30 minutes between each application, and curing at room temperature for 1 to 2 hours to obtain a micron-sized black thermal control coating with a gradient distribution of filler content;
[0011] (4) Weighing space-grade silicone resin and nano-scale high-blackness filler at a pigment-base mass ratio of 2:1 to 3.5:1, adding an organic solvent whose mass is 8 to 10 times the total mass of the space-grade silicone resin and the nano-scale high-blackness filler, and evenly dispersing to obtain a nano-scale black thermal control coating component A, adding a platinum catalyst component B whose mass is 0.3 to 1.0% of the space-grade silicone resin, and stirring to obtain an NC black thermal control coating, coating the evenly mixed NC black thermal control coating on the surface of the micron-scale black thermal control coating obtained in step (3), and curing at room temperature for 48 to 96 hours to obtain an intermediate layer with a micro-nano structure;
[0012] (5) Fully mixing the fluorine-containing polymer and the solvent, coating the uniformly mixed fluorine-containing polymer on the intermediate layer obtained in step (4), and curing at room temperature for more than 24 hours to obtain an easy-to-clean surface layer, and finally obtaining an anti-fouling black thermal control coating.
[0013] The thickness of the anti-fouling black thermal control coating is 60-80 μm, wherein the thickness of the matching bottom layer is 2-5 μm, the thickness of the middle layer is 40-60 μm, and the thickness of the easy-to-clean surface layer is between 5-15 μm.
[0014] The primer in step (1) is AC-78 primer, SS-4155 primer or Primer-G790 primer.
[0015] The space-grade silicone resin, micron-grade high-blackness filler and organic solvent in step (2) are mixed by at least one of ball milling, three-roller rolling and high-speed dispersion.
[0016] The preparation method of the space-grade silicone resin is as follows:
[0017] (1) A dry sealed reaction bottle is cooled to 0-5° C. by a dry ice / acetone bath, 50-80 g of cyclopentene and 0.3-0.7% of the total reactant mass of a platinum catalyst are added, and nitrogen is introduced into the bottle at the same time; then 100-150 g of condensed dichlorosilane is added to the reaction bottle, and after the reaction bottle is allowed to stand and warm to room temperature, an oil bath is heated to 100-120° C. and kept warm for 18-24 hours, and then the reaction bottle is cooled to room temperature to obtain a light yellow transparent liquid, the reaction bottle is evacuated and heated to 170-200° C., kept warm for more than 10 minutes, and cooled to room temperature to obtain product S1;
[0018] (2) A total of 150 to 200 ml of a saturated sodium bicarbonate aqueous solution and diethyl ether in a mass ratio of 5:1 to 2:1 are added to a reaction flask, and then a diethyl ether solution containing 30 to 50 g of the product S1 is slowly added dropwise, stirred at room temperature for more than 15 minutes, and then water and diethyl ether are evaporated to obtain the product S2;
[0019] (3) 100-150 g of cyclopentene and 0.3-0.7% of the total mass of platinum catalyst are added to a reaction bottle, nitrogen is passed through and heated to 100-120° C., then 30-70 g of product S2 is slowly added dropwise, stirred and reacted for more than 24 hours to obtain a transparent viscous liquid, slowly evacuated and heated to 170-200° C., kept warm for more than 10 minutes, and cooled to room temperature to obtain product S3;
[0020] (4) 10-20 g of S2, 50-100 g of S3 and Amberlyst 15 ion exchange resin were stirred and mixed uniformly, heated to 60-100° C. under a nitrogen atmosphere, and reacted for more than 4 hours to obtain hydrogen-containing polysiloxane S4;
[0021] (5) Add 250-350 g of octamethylcyclotetrasiloxane and a methanol solution containing 0.4-1.5 g of (CH3)4NOH into a reaction flask, remove moisture and methanol in the system, pass nitrogen and heat to 80-100° C., and when the viscosity of the system increases by 200%-500%, add 1-2 g of a capping agent 1,1,3,3-tetramethyl-1,3-divinyldisiloxane, then heat to 100-120° C. and keep warm for more than 4 hours; continue to heat to 160-180° C. and keep warm for 50-70 minutes; finally, slowly evacuate and heat to 170-200° C. and keep warm for more than 10 minutes; then cool to room temperature to obtain vinyl-containing siloxane S5;
[0022] (6) 60-100 g of vinyl siloxane S5 is added to a reaction flask and heated to 80-120° C.; then a xylene solution of MQ silicone resin having a vinyl content of 2-3% and a solute content of 40-60% is added dropwise, followed by constant temperature stirring for more than 15 minutes, slowly evacuating and heating to 120-140° C., keeping the temperature for more than 10 minutes, and cooling to room temperature to obtain a vinyl siloxane product S6;
[0023] (7) The hydrogen-containing polysiloxane S4 and the vinyl-containing polysiloxane product S6 are mixed evenly in a ratio of hydrogen to vinyl of 1.3 to 1.5, and 0.3 to 1.0% of the total mass of a platinum catalyst is added and mixed evenly to obtain a space-grade silicone resin.
[0024] The micron-sized high-blackness filler described in step (2) includes at least one of micron-sized high-blackness carbon black, carbon fiber and carbon nanotube.
[0025] The nanoscale high-blackness filler described in step (4) includes at least one of nanoscale high-blackness carbon black and graphene.
[0026] The fluorine-containing polymer in step (5) includes at least one of fluorine-containing polyether, fluorine-containing olefin and fluorocarbon.
[0027] Compared with the prior art, the present invention has at least the following beneficial effects:
[0028] (1) The present invention designs a multi-layer thermal control coating system, including a three-layer structure of a matching bottom layer, a high absorption ratio middle layer and an easy-to-clean surface layer: the matching bottom layer enables the black thermal control coating of the present invention to have good adhesion on metals, ceramics and resin-based composite materials; the high absorption ratio middle layer enables the black thermal control coating of the present invention to have a high absorption ratio and good spatial stability; the easy-to-clean surface layer enables the black thermal control coating of the present invention to have good anti-fouling properties, and when it is contaminated during ground storage, it can be wiped clean with solvents such as anhydrous ethanol or acetone, and this layer is easily eroded by atomic oxygen bombardment in the space environment, which does not affect the thermal radiation performance and spatial stability of the black thermal control coating in the service environment.
[0029] (2) The present invention designs and synthesizes a new type of silicone resin with high spatial stability, so that the black thermal control coating has both excellent mechanical properties and long life in the space environment. The solar absorption ratio of the new type of silicone resin with high spatial stability is less than or equal to 0.01. After 20 years of comprehensive irradiation in the low-orbit satellite space environment, there is no cracking or falling off, and it has good radiation resistance.
[0030] (3) The present invention designs a multi-scale micro-nano black filler type compound and content gradient distribution. The scales of the micro-structure and nano-structure can be controlled by adjusting parameters such as the shape, particle size, and aspect ratio of the filler, thereby forming a micro-nano structure with rich morphology. The incident light can be reflected and absorbed multiple times to obtain a higher absorption ratio. For the black coating that provides the micro-structure, a structure with a gradient increase in filler content from bottom to top is designed, which effectively improves the bonding strength with the primer while ensuring that the coating that contacts the incident light has a high content of black filler, effectively balancing the relationship between strong adhesion and high absorption of the coating.
[0031] (4) The present invention optimizes the coating process of the multi-layer thermal control coating system. By studying the effects of coating viscosity, spraying interval time, coating thickness per coat, and total spraying thickness on coating performance, the performance differences of different batches of coatings are controlled, thereby improving the coating coating stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a schematic diagram of the structure of the anti-fouling black thermal control coating of the present invention;
[0033] Figure 2 This is the SEM test result of the middle layer of the anti-fouling black thermal control coating in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments:
[0035] Figure 1 Shown is a schematic diagram of the structure of the anti-fouling black thermal control coating of the present invention. In the left figure, 1 is a matching bottom layer, 2 is a high absorption ratio middle layer, 3 is an easy-to-clean surface layer, and the right figure is a schematic diagram of the structure of the high absorption ratio middle layer. There are four layers in total, ① to ③ are micron-level thermal control coatings with a gradient increase in filler content, and ④ is a nano-level black thermal control coating.
[0036] Example 1
[0037] (1) Preparation of matching bottom layer: Primer-G790 was sprayed on the surface of the substrate using a compressed air spray gun. The coating was sprayed once. The coating was left to stand at room temperature for 2 h. The coating thickness was tested to be 5 μm.
[0038] (2) Preparation of new silicone resin monomers with high steric stability:
[0039] ① Cool the dry and sealed stainless steel reaction bottle to 0°C in a dry ice / acetone bath, add 70g of cyclopentene and 0.5% of the total mass of platinum catalyst, and pass nitrogen at the same time. Add 130g of condensed dichlorosilane to the reaction bottle. After the reaction bottle is warmed to room temperature, start oil bath heating to 120°C and react for 24 hours. Then cool the reaction bottle to room temperature to obtain a light yellow transparent liquid. Slowly evacuate the product and heat it to 200°C, keep it warm for more than 10 minutes, and cool it to room temperature to obtain product S1.
[0040] ② Add 170 ml of saturated sodium bicarbonate aqueous solution and ether (mass ratio 3:1) into a reaction bottle equipped with a condenser, nitrogen and a dropping funnel. Then slowly drop 50 g of S1 in ether solution and stir at room temperature for 20 minutes. Then remove the solvent by rotary evaporation to obtain a transparent liquid product S2.
[0041] ③ Add 120g of cyclopentene and 0.5% of the total mass of platinum catalyst to a reaction bottle equipped with a condenser, nitrogen and a dropping funnel. Pass nitrogen and heat to 120°C, then slowly drop 50g of product S2, stir and react for 28 hours to obtain a transparent viscous liquid. Slowly evacuate the product and heat to 180°C, keep warm for 10 minutes. Cool to room temperature to obtain product S3.
[0042] ④ 17 g of S2, 90 g of S3 and Amberlyst 15 ion exchange resin were stirred and mixed evenly, nitrogen was passed through, heated to 80°C, and reacted for 5 hours to obtain hydrogen-containing polysiloxane S4.
[0043] ⑤ Add 320g of octamethylcyclotetrasiloxane and 1g of (CH3)4NOH in methanol to a reaction bottle equipped with a condenser and nitrogen, and remove the water and methanol in the system for about 1h. Pass nitrogen and heat to 90℃. When the viscosity of the system suddenly increases, add 1g of the end-capping agent 1,1,3,3-tetramethyl-1,3-divinyldisiloxane, then heat to 120℃ and keep warm for 5 hours. Then continue to heat the system to 170℃ to decompose the catalyst for 1h. Finally, slowly evacuate the product and heat to 180℃, and keep warm for 15 minutes. Cool to room temperature to obtain vinyl-containing siloxane S5.
[0044] ⑥ Add 70g of vinyl siloxane S5 to the reaction bottle. Heat to 120℃; then slowly drop a xylene solution of MQ silicone resin containing 3% vinyl content and 50% solute content, and continue to stir at constant temperature for 20 minutes after the drop is completed. Finally, the product is slowly evacuated and heated to 140℃, and kept warm for 20 minutes. Cool to room temperature to obtain the vinyl siloxane product S6.
[0045] ⑦ The hydrogen-containing polysiloxane S4 and the vinyl-containing polysiloxane product S6 are mixed evenly at a molar ratio of n(Si-H) / n(Si-Vi) of 1.3 to obtain a space-grade silicone resin monomer.
[0046] (3) The preparation of the high absorption ratio intermediate layer is carried out in the following three steps:
[0047] ① According to the formula in Table 1, space-grade silicone resin, multi-walled carbon nanotubes with a length of 10 to 30 μm and a diameter of 20 to 30 nm, and xylene were weighed respectively, and evenly mixed by ball milling for 2 h to obtain micron-grade black thermal control coating components A1, A2, and A3.
[0048] Table 1
[0049]
[0050] ② Add 0.04 g of platinum catalyst B component to the A1 component of the micron-level black thermal control coating and stir evenly to obtain MC1 black thermal control coating, adjust the coating's coating viscosity of 4 cups to 24s, and spray it to the surface of the primer layer with a compressed air spray gun, with an interval of 15 minutes between each spraying; add 0.04 g of platinum catalyst B component to the A2 component of the micron-level black thermal control coating and stir evenly to obtain MC2 black thermal control coating, adjust the coating's coating viscosity of 4 cups to 24s, and spray it to the surface of the MC1 layer with a compressed air spray gun, with an interval of 15 minutes between each spraying; add 0.04 g of platinum catalyst B component to the A3 component of the micron-level black thermal control coating and stir evenly to obtain MC3 black thermal control coating, adjust the coating's coating viscosity of 4 cups to 24s, and spray it to the surface of the MC2 layer with a compressed air spray gun, with an interval of 15 minutes between each coat; cure at room temperature for 2 hours to obtain a micron-level black thermal control coating;
[0051] ③ Take 5g of space-grade silicone resin, 1.5g of nano-carbon black with a particle size of 50nm and 70g of xylene and obtain the nano-scale black thermal control coating component A by ultrasonic dispersion for 1h, add 0.03g of platinum catalyst component B and stir evenly, spray the evenly mixed nano-scale black thermal control coating on the surface of the micron-scale black thermal control coating, with an interval of 15min between each coat, and cure at room temperature for 72h to obtain a high absorption ratio intermediate layer with a micro-nano structure. The total thickness of the coating is tested to be 50-56μm.
[0052] (4) Easy-to-clean surface layer: Mix polytetrafluoroethylene and DMF thoroughly, and use a compressed air spray gun to spray the evenly mixed coating onto the high absorption ratio middle layer for a total of 3 times. Dry and cure at room temperature for more than 24 hours.
[0053] Figure 2 This is the SEM test result of the middle layer of the anti-fouling black thermal control coating in Example 1 of the present invention. The basic properties of the anti-fouling, long-life, high-absorption ratio black thermal control coating prepared in Example 1 are shown in Table 2:
[0054] Table 2
[0055]
[0056]
[0057] Experiments show that the thermal control coating has high absorptivity and emissivity, meeting the requirements of high absorption ratio; it has excellent adhesion to metal and non-metal substrates, good flexibility, and can withstand long-term hot and cold cycles; the total mass loss TML and condensable volatiles CVCM meet the outgassing requirements of space environment coatings in vacuum in the QJ1558A-2012 standard (TML≤1.0%, CVCM≤0.1%); at the same time, after undergoing a comprehensive irradiation test simulating 20 years of space irradiation conditions, the absorptivity and emissivity of the coating change little, with high spatial stability, meeting the requirements of long life; in addition, the thermal control coating has a contamination resistance grade of 0 and has good anti-contamination performance.
[0058] Example 2
[0059] (1) Matching base layer: Use a compressed air spray gun to spray SS-4155 one-component silicone resin primer on the surface of the substrate for one coat. The coating is left to dry at room temperature for 2 hours. The coating thickness is tested to be 3 μm.
[0060] (2) Preparation of new silicone resin monomers with high steric stability:
[0061] ① Cool the dry and sealed stainless steel reaction bottle to 2°C in a dry ice / acetone bath, add 60g of cyclopentene and 0.5% of the total mass of platinum catalyst, and pass nitrogen at the same time. Add 120g of condensed dichlorosilane to the reaction bottle. After the reaction bottle is warmed to room temperature, start oil bath heating to 110°C and react for 24 hours. Then cool the reaction bottle to room temperature to obtain a light yellow transparent liquid. Slowly evacuate the product and heat it to 180°C for more than 10 minutes, and cool it to room temperature to obtain product S1.
[0062] ② Add 170 ml of saturated sodium bicarbonate aqueous solution and ether (mass ratio 4:1) into a reaction bottle equipped with a condenser, nitrogen and a dropping funnel. Then slowly drop 45 g of S1 in ether solution and stir at room temperature for 15 minutes. Then remove the solvent by rotary evaporation to obtain a transparent liquid product S2.
[0063] ③ Add 130g of cyclopentene and 0.5% of the total mass of platinum catalyst into a reaction bottle equipped with a condenser, nitrogen and a dropping funnel. Pass nitrogen and heat to 120°C, then slowly drop 60g of product S2, stir and react for 28 hours to obtain a transparent viscous liquid. Slowly evacuate the product and heat to 180°C, keep warm for 20 minutes. Cool to room temperature to obtain product S3.
[0064] ④ 15 g of S2, 80 g of S3 and Amberlyst 15 ion exchange resin were stirred and mixed evenly, nitrogen was passed through, heated to 80°C, and reacted for 4.5 hours to obtain hydrogen-containing polysiloxane S4.
[0065] ⑤ Add 300g of octamethylcyclotetrasiloxane and 0.9g of (CH3)4NOH in methanol to a reaction bottle equipped with a condenser and nitrogen. Remove moisture and methanol from the system for about 1 hour. Pass nitrogen and heat to 90°C. When the viscosity of the system suddenly increases, add 1g of the end-capping agent 1,1,3,3-tetramethyl-1,3-divinyldisiloxane, then heat to 110°C and react for 6 hours. Then continue to heat the system to 170°C to decompose the catalyst for about 1 hour. Finally, slowly evacuate the product and heat to 180°C, keeping it warm for 20 minutes. Cool to room temperature to obtain vinyl-containing siloxane S5.
[0066] ⑥ Add 70g of vinyl siloxane S5 to the reaction bottle. Heat to 115°C; then slowly drop MQ silicone resin containing 3% vinyl content and 50% solute content, and continue to stir at constant temperature for 15 minutes after the drop is completed. Finally, the product is slowly evacuated and heated to 140°C, and kept warm for 15 minutes. Cool to room temperature to obtain the vinyl siloxane product S6.
[0067] ⑦ The hydrogen-containing polysiloxane S4 and the vinyl-containing polysiloxane product S6 are mixed evenly at a molar ratio of n(Si-H) / n(Si-Vi) of 1.3 to obtain a space-grade silicone resin monomer.
[0068] (3) The preparation of the high absorption ratio intermediate layer is carried out in the following three steps:
[0069] ① According to the formula in Table 3, space-grade silicone resin, 200 μm chopped carbon fiber and xylene were weighed respectively, and evenly mixed by three-roll rolling for 40 min + ball milling for 2 h to obtain micron-grade black thermal control coating A1, A2 and A3 components.
[0070] Table 3
[0071]
[0072] ② Add 0.03g of platinum catalyst B component to the A1 component of the micron-level black thermal control coating and stir evenly to obtain MC1 black thermal control coating, adjust the coating's coating viscosity of 4 cups to 27s, and spray it to the surface of the primer layer with a compressed air spray gun, with an interval of 15min between each spraying; add 0.03g of platinum catalyst B component to the A2 component of the micron-level black thermal control coating and stir evenly to obtain MC2 black thermal control coating, adjust the coating's coating viscosity of 4 cups to 30s, and spray it to the surface of the MC1 layer with a compressed air spray gun, with an interval of 15min between each spraying; add 0.07g of platinum catalyst B component to the A3 component of the micron-level black thermal control coating and stir evenly to obtain MC3 black thermal control coating, adjust the coating's coating viscosity of 4 cups to 33s, and spray it to the surface of the MC2 layer with a compressed air spray gun, with an interval of 17min between each coat; cure at room temperature for 2h to obtain a micron-level black thermal control coating;
[0073] ③ Take 5g of space-grade silicone resin, 2g of multilayer graphene with a thickness of 1.5-3nm and a flake diameter of 200-300nm, and 70g of xylene and obtain the nanoscale black thermal control coating component A by ultrasonic dispersion for 1h, add 0.03g of platinum catalyst component B and stir evenly, spray the evenly mixed nanoscale black thermal control coating on the surface of the micron-scale black thermal control coating, with an interval of 15min between each coat, and cure at room temperature for 72h to obtain a high absorption ratio intermediate layer with a micro-nano structure. After testing, the total thickness of the primer + intermediate layer is 58-64μm.
[0074] (4) Easy-to-clean surface layer: Mix perfluoropolyether and deionized water thoroughly, and spray the mixed coating onto the high absorption ratio intermediate layer with a compressed air spray gun for 3 times in total. Dry and cure at room temperature for more than 24 hours. The basic performance of the anti-fouling, long-life, high absorption ratio black thermal control coating was measured, and the results are shown in Table 4.
[0075] Table 4
[0076]
[0077] Example 3
[0078] (1) Matching base layer: Use a compressed air spray gun to spray AC-78 silicone resin primer on the surface of the substrate. Spray once. Let the coating stand at room temperature for 2 hours. The coating thickness is tested to be 5 μm.
[0079] (2) Preparation of new silicone resin monomers with high steric stability:
[0080] ① Cool the dry and sealed stainless steel reaction bottle to 0°C in a dry ice / acetone bath, add 80g of cyclopentene and 0.5% of the total mass of platinum catalyst, and pass nitrogen at the same time. Add 150g of condensed dichlorosilane to the reaction bottle. After the reaction bottle is warmed to room temperature, start oil bath heating to 120°C and react for 20 hours. Then cool the reaction bottle to room temperature to obtain a light yellow transparent liquid. Slowly evacuate the product and heat it to 200°C, keep it warm for 30 minutes, and cool it to room temperature to obtain product S1.
[0081] ② Add 180 ml of saturated sodium bicarbonate aqueous solution and ether (mass ratio 3:1) into a reaction bottle equipped with a condenser, nitrogen and a dropping funnel. Then slowly drop 50 g of S1 in ether solution and stir at room temperature for 30 minutes. Then remove the solvent by rotary evaporation to obtain a transparent liquid product S2.
[0082] ③ Add 150g of cyclopentene and 0.5% of the total mass of platinum catalyst into a reaction bottle equipped with a condenser, nitrogen and a dropping funnel. Pass nitrogen and heat to 110°C, then slowly drop 60g of S2, stir and react for 30 hours to obtain a transparent viscous liquid. Slowly evacuate the product and heat to 200°C, keep warm for 30 minutes. Cool to room temperature to obtain product S3.
[0083] ④ 20 g of S2, 100 g of S3 and Amberlyst 15 ion exchange resin were stirred and mixed evenly, nitrogen was passed through, and the mixture was heated at 60-100° C. and reacted for 8 hours to obtain hydrogen-containing polysiloxane S4.
[0084] ⑤ Add 350g of octamethylcyclotetrasiloxane and a methanol solution containing 1.4g of (CH3)4NOH to a reaction bottle equipped with a condenser and nitrogen. Remove moisture and methanol from the system for about 1 hour. Pass nitrogen and heat to 100°C. When the viscosity of the system suddenly increases, add 2g of the end-capping agent 1,1,3,3-tetramethyl-1,3-divinyldisiloxane, then heat to 120°C and react for 6 hours. Then continue to heat the system to 170°C to decompose the catalyst for about 1 hour. Finally, slowly evacuate the product and heat to 200°C, keeping it warm for 20 minutes. Cool to room temperature to obtain vinyl-containing siloxane S5.
[0085] ⑥ Add 80g of vinyl siloxane S5 to the reaction bottle. Heat to 110℃; then slowly drop MQ silicone resin containing 3% vinyl content and 50% solute content, and continue to stir at constant temperature for 45 minutes after the drop is completed. Finally, the product is slowly evacuated and heated to 140℃, and kept warm for 30 minutes. Cool to room temperature to obtain the vinyl siloxane product S6.
[0086] ⑦ The hydrogen-containing polysiloxane S4 and the vinyl-containing polysiloxane product S6 are mixed evenly at a molar ratio of n(Si-H) / n(Si-Vi) of 1.5 to obtain a space-grade silicone resin monomer.
[0087] (3) The preparation of the high absorption ratio intermediate layer is carried out in the following three steps:
[0088] ① According to the formula in Table 5, space-grade silicone resin, 200 μm chopped carbon fiber and xylene were weighed respectively, and evenly mixed by three-roll rolling for 40 min + ball milling for 2 h to obtain micron-grade black thermal control coating A1, A2 and A3 components.
[0089] Table 5
[0090]
[0091] ② Add 0.04g of platinum catalyst B component to the A1 component of the micron-level black thermal control coating and stir evenly to obtain MC1 black thermal control coating, adjust the coating's coating viscosity of 4 cups to 24s, and spray it to the surface of the primer layer with a compressed air spray gun, with an interval of 15min between each spraying; add 0.04g of platinum catalyst B component to the A2 component of the micron-level black thermal control coating and stir evenly to obtain MC2 black thermal control coating, adjust the coating's coating viscosity of 4 cups to 28s, and spray it to the surface of the MC1 layer with a compressed air spray gun, with an interval of 15min between each spraying; add 0.04g of platinum catalyst B component to the A3 component of the micron-level black thermal control coating and stir evenly to obtain MC3 black thermal control coating, adjust the coating's coating viscosity of 4 cups to 31s, and spray it to the surface of the MC2 layer with a compressed air spray gun, with an interval of 15min between each coat; cure at room temperature for 2h to obtain a micron-level black thermal control coating;
[0092] ③ Take 5g of space-grade silicone resin, 2g of high-blackness carbon black with a particle size of 50nm and 70g of xylene and obtain the nano-scale black thermal control coating component A by ultrasonic dispersion for 1h, add 0.03g of platinum catalyst component B and stir evenly, spray the evenly mixed nano-scale black thermal control coating on the surface of the micron-scale black thermal control coating, with an interval of 15min between each coat, and cure at room temperature for 72h to obtain a high absorption ratio intermediate layer with a micro-nano structure. The total thickness of the coating is tested to be 51-57μm.
[0093] (4) Easy-to-clean surface layer: Take the polyvinylidene fluoride suspension and DMF and mix them thoroughly. Use a compressed air spray gun to spray the mixed coating onto the high absorption ratio middle layer. Spray it twice in total and let it stand at room temperature for more than 24 hours. The basic performance of the anti-fouling, long-life, high absorption ratio black thermal control coating was measured. The results are shown in Table 6.
[0094] Table 6
[0095]
[0096]
[0097] In summary, the anti-fouling, long-life, high-absorption-ratio black thermal control coating prepared by the present invention has an absorption ratio greater than or equal to 0.98, an emissivity greater than or equal to 0.92, a contamination resistance level of 0, an adhesion level less than or equal to 1, and little degradation of light absorption performance after space environment irradiation test, thus meeting the demand of satellite products for black thermal control coatings for space use.
[0098] The above description is only the best specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
[0099] The contents not described in detail in the specification of the present invention belong to the common knowledge of the professionals in this field.
Claims
1. A method for preparing an anti-fouling black thermal control coating, characterized in that: The following steps are involved: (1) applying a primer to the surface of a substrate with a coating thickness of 2 to 5 μm, and leaving it in the air at room temperature for 20 to 24 hours to obtain a matching base layer; (2) Weighing space-grade silicone resin and micron-grade high-blackness filler at a pigment-base mass ratio of 10:1-12:1, 5:1-8:1 and 2:1-3:1, respectively, adding an organic solvent whose total mass is 8-10 times that of the space-grade silicone resin and the micron-grade high-blackness filler, and uniformly mixing to obtain micron-grade black thermal control coating A1, A2 and A3 components, adjusting the coating-4 cup viscosity of the A1, A2 and A3 components to 20-40s, adding 0.3-1.0% of the mass of the space-grade silicone resin platinum catalyst B component, respectively, and stirring to obtain MC1, MC2 and MC3 black thermal control coatings; (3) applying the uniformly mixed black thermal control coatings MC1 to MC3 obtained in step (2) to the matching bottom layer obtained in step (1) in sequence, with an interval of 10 to 30 minutes between each application, and curing at room temperature for 1 to 2 hours to obtain a micron-sized black thermal control coating with a gradient distribution of filler content; (4) Weighing space-grade silicone resin and nano-scale high-blackness filler at a pigment-base mass ratio of 2:1 to 3.5:1, adding an organic solvent whose mass is 8 to 10 times the total mass of the space-grade silicone resin and the nano-scale high-blackness filler, and evenly dispersing to obtain a nano-scale black thermal control coating component A, adding a platinum catalyst component B whose mass is 0.3 to 1.0% of the space-grade silicone resin, and stirring to obtain an NC black thermal control coating, coating the evenly mixed NC black thermal control coating on the surface of the micron-scale black thermal control coating obtained in step (3), and curing at room temperature for 48 to 96 hours to obtain an intermediate layer with a micro-nano structure; (5) Fully mixing the fluorine-containing polymer and the solvent, coating the uniformly mixed fluorine-containing polymer on the intermediate layer obtained in step (4), and curing at room temperature for more than 24 hours to obtain an easy-to-clean surface layer, and finally obtaining an anti-fouling black thermal control coating.
2. The method for preparing an anti-fouling black thermal control coating according to claim 1, characterized in that: The thickness of the anti-fouling black thermal control coating is 60-80 μm, wherein the thickness of the matching bottom layer is 2-5 μm, the thickness of the middle layer is 40-60 μm, and the thickness of the easy-to-clean surface layer is between 5-15 μm.
3. The method for preparing an anti-fouling black thermal control coating according to claim 1, characterized in that: The primer in step (1) is AC-78 primer, SS-4155 primer or Primer-G790 primer.
4. The method for preparing an anti-fouling black thermal control coating according to claim 1, characterized in that: The space-grade silicone resin, micron-grade high-blackness filler and organic solvent in step (2) are mixed by at least one of ball milling, three-roller rolling and high-speed dispersion.
5. The method for preparing an anti-fouling black thermal control coating according to claim 1, characterized in that: The preparation method of the space-grade silicone resin is as follows: (1) A dry sealed reaction bottle is cooled to 0-5° C. by a dry ice / acetone bath, 50-80 g of cyclopentene and 0.3-0.7% of the total reactant mass of a platinum catalyst are added, and nitrogen is introduced into the bottle at the same time; then 100-150 g of condensed dichlorosilane is added to the reaction bottle, and after the reaction bottle is allowed to stand and warm to room temperature, an oil bath is heated to 100-120° C. and kept warm for 18-24 hours, and then the reaction bottle is cooled to room temperature to obtain a light yellow transparent liquid, the reaction bottle is evacuated and heated to 170-200° C., kept warm for more than 10 minutes, and cooled to room temperature to obtain product S1; (2) A total of 150 to 200 ml of a saturated sodium bicarbonate aqueous solution and diethyl ether in a mass ratio of 5:1 to 2:1 are added to a reaction flask, and then a diethyl ether solution containing 30 to 50 g of the product S1 is slowly added dropwise, stirred at room temperature for more than 15 minutes, and then water and diethyl ether are evaporated to obtain the product S2; (3) 100-150 g of cyclopentene and 0.3-0.7% of the total mass of platinum catalyst are added to a reaction bottle, nitrogen is passed through and heated to 100-120° C., then 30-70 g of product S2 is slowly added dropwise, stirred and reacted for more than 24 hours to obtain a transparent viscous liquid, slowly evacuated and heated to 170-200° C., kept warm for more than 10 minutes, and cooled to room temperature to obtain product S3; (4) 10-20 g of S2, 50-100 g of S3 and Amberlyst 15 ion exchange resin were stirred and mixed uniformly, heated to 60-100° C. under a nitrogen atmosphere, and reacted for more than 4 hours to obtain hydrogen-containing polysiloxane S4; (5) Add 250-350 g of octamethylcyclotetrasiloxane and a methanol solution containing 0.4-1.5 g of (CH3)4NOH into a reaction flask, remove moisture and methanol in the system, pass nitrogen and heat to 80-100° C., and when the viscosity of the system increases by 200%-500%, add 1-2 g of a capping agent 1,1,3,3-tetramethyl-1,3-divinyldisiloxane, then heat to 100-120° C. and keep warm for more than 4 hours; continue to heat to 160-180° C. and keep warm for 50-70 minutes; finally, slowly evacuate and heat to 170-200° C. and keep warm for more than 10 minutes; then cool to room temperature to obtain vinyl-containing siloxane S5; (6) 60-100 g of vinyl siloxane S5 is added to a reaction flask and heated to 80-120° C.; then a xylene solution of MQ silicone resin having a vinyl content of 2-3% and a solute content of 40-60% is added dropwise, followed by constant temperature stirring for more than 15 minutes, slowly evacuating and heating to 120-140° C., keeping the temperature for more than 10 minutes, and cooling to room temperature to obtain a vinyl siloxane product S6; (7) The hydrogen-containing polysiloxane S4 and the vinyl-containing polysiloxane product S6 are mixed evenly in a ratio of hydrogen to vinyl of 1.3 to 1.5, and 0.3 to 1.0% of the total mass of a platinum catalyst is added and mixed evenly to obtain a space-grade silicone resin.
6. The method for preparing an anti-fouling black thermal control coating according to claim 1, characterized in that: The micron-sized high-blackness filler described in step (2) includes at least one of micron-sized high-blackness carbon black, carbon fiber and carbon nanotube.
7. The method for preparing an anti-fouling black thermal control coating according to claim 1, characterized in that: The nanoscale high-blackness filler described in step (4) includes at least one of nanoscale high-blackness carbon black and graphene.
8. The method for preparing an anti-fouling black thermal control coating according to claim 1, characterized in that: The fluorine-containing polymer in step (5) includes at least one of fluorine-containing polyether, fluorine-containing olefin and fluorocarbon.
9. An anti-fouling black thermal control coating, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Inorganic ultra-black thermal control coating with high absorption, high incidence and low condensable volatile matter content and preparation method of inorganic ultra-black thermal control coating
CN116855106A
Ultra-black light absorbing coating with stable mechanical property as well as preparation method and application of ultra-black light absorbing coating
CN117701144A